Fluidic Flow Enhances the Differentiation of Placental Trophoblast-Like 3D Tissue from hiPSCs in a Perfused Macrofluidic Device - Deng, Pengwei; Cui, Kangli; Shi, Yang; Zhu, Yujuan; Wang, Yaqing; Shao, Xiaoguang; Qin, Jianhua (Frontiers in Bioengineering and Biotechnology, 2022)
The human placenta serves as a multifunctional organ to maintain the proper development of fetus. However, our knowledge of the human placenta is limited due to the lack of appropriate experimental models. In this work, we created an in vitro placental trophoblast-like model via self-organization of human pluripotent stem cells (hiPSCs) in a perfused 3D culture macrofluidic device. This device allowed cell seeding, in situ trophoblast lineage differentiation and formation of trophoblasts-like tissues from hiPSCs in a biomimetic microenvironment. It incorporated extracellular matrix (ECM) and fluid flow in a single device. After trophoblast lineage differentiation, we were able to generate the 3D clusters with major cell types of human placenta, including trophoblast progenitors cytotrophoblasts (CTBs), differentiated subtypes syncytiotrophoblasts (STBs) and extravillous trophoblasts (EVTs) under long term 3D culture (~23 days). Moreover, the formed tissues exhibited enhanced expressions of CTBs-, STBs- and EVTs-related markers at the level of genes and proteins under dynamic culture compared to static condition. RNA-seq analysis revealed the higher expression of trophoblast-specific genes in 3D tissues, indicating the essential role of fluid flow to promote the trophoblast differentiation of hiPSCs. The established placental 3D model combined bioengineering strategy with developmental principles, providing a promising platform for the study of placental biology in a biomimetic microenvironment in health and disease.